The Perception over Corporate Social Responsibility in România - Nicolae BIBU; Marian NĂSTASE; Diana Corina GLIGOR (Revista de Management Comparat International)
The new international economic context can determine a turning point for many business organizations. The „crisis” term can be perceived as a threat or an opportunity, but in our opinion it represents a test. The test which business organizations in Romania will have to pass in terms of corporate social responsibility is the meaning that will give it during the next period. The two main future directions in our view are diametrically opposed: either the role of corporate social responsibility will increase as proof of the truthfulness and authenticity of the past, present and future efforts, or the budgets of corporate social responsibility programs will be entered as reduced expenditures or even eliminated. We believe that policies are determined by the perception of corporate social responsibility for the managers of existing companies that have implemented and implement corporate social responsibility programs. It is therefore very important to know that perception and try to anticipate its future implications. By this work we try to capture some aspects of the perception of corporate social responsibility in Romania in the period before the onset current international economic crisis and to anticipate the direction that corporate social responsibility programs in Romania will follow.